Eksperimentasi Model Pembelajaran Self-Direct Learning dengan Media Pembelajaran Berbasis Komik Digital - Ayis Crusma Fradani; Fruri Stevani; Agus Kurniawan (UIR Press, 2022)
Independent learning is one solution that can be applied in the unfinished pandemic period, which requires online learning like now. Independent learning also creates problems because it must match the model or media used so that learning outcomes can be achieved. Appropriate learning models and media are expected to improve student learning outcomes. Based on this, this research is needed to determine the effect of the Self-Direct Learning learning model combined with digital comic learning media on the learning outcomes of the Techno-Edupreneurship course in 4th semester students of the English Education Study Program at IKIP PGRI Bojonegoro for the academic year 2020/2021 by comparing the learning outcomes obtained through these methods and media with the learning outcomes of direct learning. This research is a quasi-experimental research conducted to compare one or more comparison groups that received other treatments. The results of this study indicate that there is a comparison of the learning outcomes of the Self-Direct Learning learning model combined with digital comics learning media to obtain a higher average score than direct learning